ANT COLONY OPTIMIZATION TO DETERMINE THE SHORTEST ROUTE OF TOURIST DESTINATIONS IN BALI : A CASE STUDY - I Gede Susrama Mas Diyasa (Jurnal Ilmiah Kursor, 2022)
Bali is one of the popular tourist destinations in Indonesia. As technology develops, the tourism sector also gets support in the process. The problem we address in this research is to determine the closest distance to travel in Bali. The purpose of this study is to assist users in deciding which route is better to visit first so that it is more effective in terms of energy, gasoline usage, and time. We proposed a shortest route system using ant colony optimization (ACO). ACO then compared with other optimization method. ACO produces a great result with the optimal distance and reasonable amount of search time.